Final stage of cathode directed streamer propagation - Bolotov, O.; Kadolin, B.; Mankovskyi, S.; Ostroushko, V.; Pashchenko, I.; Taran, G.; Zavada, L. (Вопросы атомной науки и техники, 2016)
The numerical simulations of the cathode directed streamer propagation in the atmospheric air at the constant
voltage applied to the discharge gap are carried out. It is found an explanation of the streamer stopping possibility at
the given distance from electrodes achieved in experiment. For the streamers, which cross the gap, it is obtained the
transverse ionization wave propagation, which gives a contribution to the second maximum of the total current time
dependence. Выполнено численное моделирование катодонаправленного стримера в атмосферном воздухе при
постоянном напряжении, приложенном к разрядному промежутку. Найдено пояснение возможности
останавливать стример на данном расстоянии от электродов, достигнутой в эксперименте. Для стримеров,
которые пересекают промежуток, получено поперечное распространение волны ионизации, которое даёт
вклад во второй максимум зависимости полного тока от времени. Виконане числове моделювання катодоспрямованого стримера в атмосферному повітрі при постійній
напрузі, докладеній до розрядного проміжку. Знайдене пояснення можливості зупиняти стример на даній
відстані від електродів, досягнутої у експерименті. Для стримерів, які перетинають проміжок, отримане
поперечне поширення хвилі іонізації, яке дає внесок у другий максимум залежності повного струму від
часу.